Interaction between mouse adenovirus type 1 and cell surface heparan sulfate proteoglycans. - Liesbeth Lenaerts (Public Library of Science (PLoS), 2012)
Application of human adenovirus type 5 (Ad5) derived vectors for cancer gene therapy has been limited by the poor cell surface expression, on some tumor cell types, of the primary Ad5 receptor, the coxsackie-adenovirus-receptor (CAR), as well as the accumulation of Ad5 in the liver following interaction with blood coagulation factor X (FX) and subsequent tethering of the FX-Ad5 complex to heparan sulfate proteoglycan (HSPG) on liver cells. As an alternative vector, mouse adenovirus type 1 (MAV-1) is particularly attractive, since this non-human adenovirus displays pronounced endothelial cell tropism and does not use CAR as a cellular attachment receptor. We here demonstrate that MAV-1 uses cell surface heparan sulfate proteoglycans (HSPGs) as primary cellular attachment receptor. Direct binding of MAV-1 to heparan sulfate-coated plates proved to be markedly more efficient compared to that of Ad5. Experiments with modified heparins revealed that the interaction of MAV-1 to HSPGs depends on their N-sulfation and, to a lesser extent, 6-O-sulfation rate. Whereas the interaction between Ad5 and HSPGs was enhanced by FX, this was not the case for MAV-1. A slot blot assay demonstrated the ability of MAV-1 to directly interact with FX, although the amount of FX complexed to MAV-1 was much lower than observed for Ad5. Analysis of the binding of MAV-1 and Ad5 to the NCI-60 panel of different human tumor cell lines revealed the preference of MAV-1 for ovarian carcinoma cells. Together, the data presented here enlarge our insight into the HSPG receptor usage of MAV-1 and support the development of an MAV-1-derived gene vector for human cancer therapy.